2022
DOI: 10.1158/0008-5472.can-21-2161
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy Controls Proteomic and Transcriptomic Pathways to Maintain Glioma Stem Cell Activity

Abstract: Chaperone-mediated autophagy (CMA) is a homeostatic process essential for the lysosomal degradation of a selected subset of the proteome. CMA activity directly depends on the levels of LAMP2A, a critical receptor for CMA substrate proteins at the lysosomal membrane. In glioblastoma (GBM), the most common and aggressive brain cancer in adulthood, high levels of LAMP2A in the tumor and tumor-associated pericytes have been linked to temozolomide resistance and tumor progression. However, the role of LAMP2A, and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Tumor cell infiltration and invasion of the brain parenchyma, which provides a proliferative environment, can occur via interaction between tumor cells and parenchyma cells such as PCs [ 17 ], creating a large network of microtubes and nanotubes that favors tumor development [ 16 , 55 ]. In addition, different cancer stem cells (CSCs) are also found in the TME, making GB difficult to treat [ 38 , 56 , 57 , 58 ]. Thus, the study of the TME, including the perivascular area with peritumoral PCs, is essential to make a good diagnosis of tumor progression.…”
Section: Cma In Pc During Gb Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cell infiltration and invasion of the brain parenchyma, which provides a proliferative environment, can occur via interaction between tumor cells and parenchyma cells such as PCs [ 17 ], creating a large network of microtubes and nanotubes that favors tumor development [ 16 , 55 ]. In addition, different cancer stem cells (CSCs) are also found in the TME, making GB difficult to treat [ 38 , 56 , 57 , 58 ]. Thus, the study of the TME, including the perivascular area with peritumoral PCs, is essential to make a good diagnosis of tumor progression.…”
Section: Cma In Pc During Gb Progressionmentioning
confidence: 99%
“…Importantly, data from our lab have shown that, in addition to upregulation of LAMP-2A expression and, therefore, increased CMA activity in tumor cells, GB-mediated upregulation of CMA in PCs is also required for tumor growth [ 17 ]. Thus, in GB, LAMP-2A has been considered a potential prognosis marker in tumorigenicity [ 38 ] as well as a predictor of poor cancer prognosis due to the tumor cell infiltration and progression driven by tumor cell–PC interactions [ 17 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the proteomics analysis highlights an IFN signaling enhancement, as well as a decreased of MHC class II antigen-presentation-what together with proinflammatory cytokines, suggest the implication of this selective autophagy pathway in the immune effect in GBM mediated by the STAT components (10). The specific critical cytokines and factors are still pending of further validation; as it is also pending to check if the effect is specific of GSCs.…”
mentioning
confidence: 99%
“…The modulation occurs in relation to different regulatory components-also to functional protein groups already described as substrates for this pathway. Those include: extra cellular matrix effectors, pathways related CMA mitochondrial metabolism and the immune system, and p53 or PI3K-AKT pathways (10). Energy homeostasis of the cells was reported during the last few years as intimately linked with the activity of CMA (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation